Complementary and alternative medicine (CAM) use and its association with antibiotic usage practices: a nationally representative population study - Tan, Shannon (2023)
Background: Inappropriate antibiotic use drives antimicrobial resistance (AMR). Complementary and alternative medicine (CAM) is often used alongside Western medicine in multi-cultural Singapore. This study aimed to assess the influence of CAM use on antibiotic usage practices. Methods: A nationally representative cross-sectional population survey was conducted in Singapore from November 2020 to January 2021. CAM use was defined as the use of traditional Chinese medicine, acupuncture, Jamu, Ayurvedic medicine or herbal remedies. Multi-variable logistic regression analysis was conducted to assess the association between CAM use and good antibiotic usage practices, as defined by six proxy statements adapted from guidance from the US Centers for Disease Control and Prevention. Sociodemographic characteristics, motivations for CAM use, and knowledge of antibiotic use and AMR were analysed. Results: Thirty-four percent of 2004 respondents used CAM. The majority of CAM users were female (CAM users 57% vs non-CAM users 50%; P=0.004), Chinese (82% vs 66%; P<0.001), had a higher level of education (68% vs 64%; P=0.036), lived in the highest tier of public housing apartments or private housing (45% vs 36%; P<0.001), and had good knowledge of antibiotic use (63% vs 58%; P=0.036). After adjusting for potential confounding, CAM use (adjusted odds ratio 1.23, 95% confidence interval 1.00–1.52; P=0.048) was associated with 23% increased odds of good antibiotic usage practices. The top reasons for CAM use included recommendations from family and friends (65%), and concern about the side effects of Western medicine (44%). Conclusion: CAM use is positively associated with good antibiotic usage practices. Further studies assessing educational interventions utilizing social networks and highlighting the side effects of antibiotics may be useful in improving antibiotic usage practices in communities.